Gender‐specific health implications of minority stress among lesbians and gay men. (3rd July 2016) - Bariola, Emily; Lyons, Anthony; Leonard, William
Abstract: Objectives : Lesbians and gay men are exposed to unique minority stressors. We examined the health implications of one type of distal minority stressor (victimisation) and one type of proximal minority stressor (sexual identity concealment due to anticipated stigma) among lesbians and gay men. Gender‐specific health implications were assessed. Methods : Data were collected via an online survey involving an Australian sample of 1, 470 gay men and 1, 264 lesbians. Survey questions assessed demographics, experiences of different forms of sexual identity‐related victimisation and sexual identity concealment in a variety of contexts. Health outcomes included self‐reported general health, illicit drug use, frequency of alcohol consumption, smoking status, and weight status. Results : Gay men reported higher rates of victimisation and identity concealment than lesbians. Controlling for demographic differences, experiences of victimisation were associated with poorer self‐rated health, illicit drug use, and smoking among both gay men and lesbians. In contrast, identity concealment was linked with poorer health outcomes among lesbians only. Conclusions : Our findings offer new insights into the potential antecedents of the health inequalities that have previously been reported for these populations.